TI na administração pública: uma visão do campo de pesquisa internacional - Silva, Ambrozina de Abreu Pereira (2019)
Although there is a vast literature on the use of Information Technology and Information Systems (IT / IS) in the public sector, it is scattered in journals in the areas of administration, public administration and information technology, which makes it difficult to consolidate knowledge in the field of research. This thesis aims to present the intellectual structure of the use of Information Technology in Public Administration condensing the last 40 years between 1980 and 2019 of publications in these areas. To represent the field of publication in the theme, a search was made in the database EBSCO (Business Source Complete; Computers & Applied Sciences Complete) and SCOPUS. The data obtained were analyzed through text mining, co-citation analysis and co-word analysis. Among the results were identified the main journals that have carried this subject. In the process of text mining the four major themes of the field were obtained, besides being indicated opportunities for future studies. In the co-word analysis, the themes found previously were detailed in a longitudinal view resulting in 20 themes studied throughout the analyzed period. In addition, the co-citation analysis evidenced the little use of theories in the field, except for theories of adoption and diffusion of innovation, which is evidence that the field is still demanding efforts to consolidate. As a main contribution, this thesis allows a better understanding of the deficiencies of the field of study and the identification of research and evolution opportunities.